2016
DOI: 10.1002/prot.25181
|View full text |Cite
|
Sign up to set email alerts
|

Double phosphorylation‐induced structural changes in the signal‐receiving domain of IκBα in complex with NF‐κB

Abstract: Activation of the transcription factor NF-κB requires degradation of its physiological inhibitor IκBα in order to allow nuclear translocation of NF-κB. NF-κB activity links inflammation and carcinogenesis and makes its signaling pathway an important target for therapeutic intervention. The signal-receiving N-terminal domain (SRD) of the NF-κB inhibitor IκBα harbors the sites of post-translational modifications (Ser32 and 36) directed by the IκB kinase (IKK) complex. The SRD was originally recognized to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
(262 reference statements)
0
14
0
Order By: Relevance
“…The IKK complex can be activated by lipopolysaccharides (LPSs), viral proteins, oxygen free radicals, cytokines and other stimuli; it then phosphorylates the Ser36 and Ser32 residues in the SRD region of the N-terminus of IκBα (Traenckner et al, 1995;Hayden and Ghosh, 2004;Kato et al, 2012;Ko et al, 2017;Liu et al, 2018;Safi et al, 2018), leading to ubiquitination and the subsequent degradation of the IκBα in proteasome (Figure 2). IKK-dependent IκBα phosphorylation at the serine residues occurring in the cytosol is a key step in the release of active NF-κB and its nuclear translocation (Yazdi et al, 2017). A molecular dynamics simulation experiment showed that IKK first phosphorylates IκBα at Ser36, changing the local conformation of the N-terminal region and increasing the relative solvent-accessible surface area of Ser32.…”
Section: Ikk-dependent Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…The IKK complex can be activated by lipopolysaccharides (LPSs), viral proteins, oxygen free radicals, cytokines and other stimuli; it then phosphorylates the Ser36 and Ser32 residues in the SRD region of the N-terminus of IκBα (Traenckner et al, 1995;Hayden and Ghosh, 2004;Kato et al, 2012;Ko et al, 2017;Liu et al, 2018;Safi et al, 2018), leading to ubiquitination and the subsequent degradation of the IκBα in proteasome (Figure 2). IKK-dependent IκBα phosphorylation at the serine residues occurring in the cytosol is a key step in the release of active NF-κB and its nuclear translocation (Yazdi et al, 2017). A molecular dynamics simulation experiment showed that IKK first phosphorylates IκBα at Ser36, changing the local conformation of the N-terminal region and increasing the relative solvent-accessible surface area of Ser32.…”
Section: Ikk-dependent Phosphorylationmentioning
confidence: 99%
“…A molecular dynamics simulation experiment showed that IKK first phosphorylates IκBα at Ser36, changing the local conformation of the N-terminal region and increasing the relative solvent-accessible surface area of Ser32. This enables Ser32 to interact with IKK via phosphorylation (Yazdi et al, 2017).…”
Section: Ikk-dependent Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that phosphorylation of the PEST sequence is not critical for the binding affinity, but only slightly increase the association rate between NF κB and IκBα by perhaps enhancing the folding mechanism of binding 64 . Casein kinase II is known to phosphorylate residues Ser283, Ser288, Thr291, Ser293, and Ser299 64 .…”
Section: Protein Structure Analysismentioning
confidence: 99%
“…IκBα in complex with NFκB is a substrate for the IKK complex. 23 , 24 Phosphorylation of IκBα prompts it for ubiquitination leading eventually to the degradation of IκBα and the release and nuclear translocation of NFκB. These steps provide another important regulatory mechanism to control the activation of NFκB signal transduction downstream of the TNFR complex.…”
Section: Introductionmentioning
confidence: 99%